(untitled) (Confluenţe Bibliologice, 2016)
Scientometrics is a useful tool for sifting values and connection with Eu-ropean values regarding basic scientiﬁc research. Scientometrics study on university researchers from Bălţi demonstrates the value of their scientiﬁc contributions.